신육성 품종인 루비에스(Ruby S; Malus pumila Mill.) 사과껍질의 항산화, 건강 기능성 및 미용식품 활성 - 이은호(Eun-Ho Lee); 김예진(Ye-Jin Kim); 권순일(Soon-Il Kwon); 김정희(Jeong-Hee Kim); 강인규(In-Kyu Kang); 정희영(Hee-Young Jung); 박경일(Kyeung-Il Park); 조영제(Young-Je Cho) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2018)
식육성 품종 루비에스 껍질의 water와 ethanol 추출물들의 항산화, 건강 기능성 및 미용식품 활성을 살펴보았다. 신육성 품종 루비에스 껍질로부터 water와 ethanol로 추출하였을 때 각각 5.29, 8.76 mg/g의 비교적 높은 phenolic 함량을 나타내었다. 루비에스 껍질 추출물의 antioxidant protection factor는 water와 ethanol 추출물 100 μg/mL phenolics 농도에서 각각 1.87, 1.77 PF를 나타내었으며, TBARS는 100 μg/mL phenolics 농도에서 water 추출물은 80.17 %, ethanol 추출물은 38.72%의 항산화능을 나타내어, 루비에스 사과 껍질 추출물의 경우 노화방지를 위한 천연 항산화제로 활용 가능성이 매우 높은 것으로 판단하였다. 루비에스 껍질 추출물의 항염증(hyaluronidase 저해) 효과는 water 및 ethanol 추출물 200 μg/mL phenolics 농도에서 각각 5.61, 31.87%의 저해 효과를 나타내었다. 통풍을 유발하는 xanthine oxidase 저해 효과는 ethanol 추출물에서만 100 μg/mL의 phenolic 농도에서 28.66%의 xanthine oxidase 저해 효과를 나타내어 대조구로 사용된 후지 품종에 비교해 상대적으로 높은 저해 효과를 나타내었다. 루비에스 껍질 추출물의 α-amylase 저해 효과는 water 추출물과 ethanol 추출물 모두 비교적 낮은 저해 효과를 나타내었으나, α- glucosidase 활성저해의 경우 200 μg/mL의 phenolic 농도에서 water와 ethanol 추출물에서 각각 94.93%와 100.00 %의 매우 높은 저해 효과를 나타내었다. 미백 효과를 측정하는 tyrosinase 저해 효과는 200 μg/mL의 phenolic 농도에서 ethanol 추출물에서만 17.50%의 저해 효과를 나타내었다. 주름 개선 효과를 나타내는 elastase 및 collagenase 저해 효과는 200 μg/mL phenolics 농도의 water 추출물에서 각각 6.70, 69.85%의 저해 효과를 나타내었고, ethanol 추출물에서 각각 41.95, 80.73%의 저해 효과를 나타내어 기능성 화장품 개발을 위한 소재로 활용 가능성이 매우 높은 것으로 판단하였다. 따라서 루비에스 껍질 추출물의 항산화, 항염증, 통풍 억제, 항당뇨, 미백 및 주름 개선 효과 및 항당뇨, 통풍 억제 효과를 확인하였고, 기존의 후지 품종과 비교해서 기능성이 더 우수함이 밝혀져 새로운 기능성 화장품 및 건강 기능성 식품 조성물로 이용이 가능할 것으로 판단되었다. In this study, the anti-oxidative, health functional, and beauty food activities of water and ethanol extracts from newly bred Ruby S apple (Malus pumila Mill.) peel. Peel of newly bred Ruby S apple was extracted using water and ethanol for extracting solvent. Water and ethanol extracts showed relatively high phenolic contents of 5.29 mg/g and 8.76 mg/g, respectively. Each water and ethanol extracts of Ruby S apple peel showed antioxidant protection factor values of 1.87 and 1.77 PF, respectively, and TBARS showed anti-oxidative effects of 80.17% and 38.76% at a phenolic concentration of 100 μg/mL. Therefore, extract of Ruby S apple peel can be considered as an anti-oxidative and anti-aging agent. The anti-inflammatory effect (hyaluronidase inhibition) of extract of Ruby S apple peel was 5.61% in water extract and 31.87% in ethanol extract both at a phenolic concentration of 200 μg/mL. Activity of xanthine oxidase, which causes gout, was inhibited by 28.66% by ethanol extract at 100 μg/mL, which was higher than other species used as a control, whereas there was no effect using water extract. Both water and ethanol extracts showed low α-amylase inhibitory effects, whereas α-glucosidase inhibitory activities were 94.93% and 100.00% at a phenolic concentration of 200 μg/mL, respectively. To measure whitening effect, tyrosinase inhibitory activity was measured, and only ethanol extract showed an inhibitory effect (17.50%). For anti-wrinkle effect, water extract showed 6.70% and 69.85% elastase and collagenase inhibitory activities, respectively, while ethanol extract showed 41.95% and 80.73% activities. These results show the high potential of Ruby S apple peel extracts as a cosmetic resource. Ruby S apple peel was identified to have various functions, including anti-oxidative, anti-inflammatory, gout preventative, whitening, anti-wrinkle, and anti-diabetic effects, which confirms that Ruby S apple peel is an outstanding species compared to other species. Therefore, Ruby S apple peel is a quality source of new functional cosmetics and can be viewed as a functional foods. KCI Citation Count: 5